2014
DOI: 10.3390/ijms15011392
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Disposal of Tumor-Suppressor miRs-145 and -34a via Microvesicles and 5-FU Resistance of Human Colon Cancer Cells

Abstract: The dysregulation of microRNA (miRNA) expression causes various kinds of diseases. Especially, alterations in miRNA expression levels are frequently observed in human tumor cells and are associated with cancer pathogenesis. Earlier we established Fluorouracil (5-FU)-resistant human colon cancer DLD-1 cells (DLD-1/5FU) from parental 5-FU- sensitive DLD-1 cells. In the present study, we examined the expression of miRNA in each cell line and in its extracellular microvesicles (MVs) before and after treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 23 publications
2
52
0
Order By: Relevance
“…Interestingly, CDF has previously been shown to reduce colonosphere formation and colon cancer cell growth when combined with 5-FU and oxaliplatin[58], suggesting that demethylation of miR-34a may be part of the mechanism underlying this effect. Independent of this study, the intracellular expression of miR-34a has been reported to be downregulated in 5-FU-resistant human colon cancer cells as compared to 5-FU-sensitive cells, with miR-34a secreted at higher rates into extracellular microvesicles in response to 5-FU treatment in 5-FU resistant versus sensitive cells[59]. Therefore, further studies investigating the sensitizing effects of miR-34a to 5-FU are warranted to determine if the combination of these agents can be used in treating colorectal cancer patients.…”
Section: The Tumor-suppressive Role Of Mir-34a In Solid Tumorsmentioning
confidence: 99%
“…Interestingly, CDF has previously been shown to reduce colonosphere formation and colon cancer cell growth when combined with 5-FU and oxaliplatin[58], suggesting that demethylation of miR-34a may be part of the mechanism underlying this effect. Independent of this study, the intracellular expression of miR-34a has been reported to be downregulated in 5-FU-resistant human colon cancer cells as compared to 5-FU-sensitive cells, with miR-34a secreted at higher rates into extracellular microvesicles in response to 5-FU treatment in 5-FU resistant versus sensitive cells[59]. Therefore, further studies investigating the sensitizing effects of miR-34a to 5-FU are warranted to determine if the combination of these agents can be used in treating colorectal cancer patients.…”
Section: The Tumor-suppressive Role Of Mir-34a In Solid Tumorsmentioning
confidence: 99%
“…Such phenomenon was observed in several tumour models, including ovarian cancer [7], prostate cancer [8, 9] and osteosarcoma [10]. In colon cancer cells, enhanced secretion of miR-145 and miR-34a via exosomes increased the cells’ resistance to 5-fluorouracil [11]. Docetaxel resistance is related to the enhancement of exosome secretion in a prostate cancer model, probably due to docetaxel efflux through exosomes [12].…”
Section: Introductionmentioning
confidence: 99%
“…Release of exosomes was shown to be a mechanism in acidosis-mediated cisplatin resistance in human melanoma cells [18, 19]. In colon cancer cells, enhanced secretion of miR-145 and miR-34a via MVs increased the cells' resistance to 5-fluorouracil [20]. In an attempt to make vehicles to deliver anticancer agents, exosomes released by mesenchymal stem cells treated with paclitaxel were found to contain paclitaxel [21].…”
Section: Introductionmentioning
confidence: 99%